SUSTAINING THE AGILITY OF SMES’ BUSINESS STRATEGY: MINIMISING THE OUTBREAK OF COVID-19 VIA CROWDSOURCING PRACTICES - Mansor, Mohd Fitri; Abu, Noor Hidayah; Halim, Hasliza Abdul; Ahmad, Noor Hazlina (CENTRAL ASIA AND THE CAUCASUS, 2021)
The spread of COVID-19 has changed many aspects of our lives in many continents. This critical situation forced many business enterprises including Small and Medium Enterprises (SMEs) require agile of their business strategy to survive in market. The emergence of Technology Web 2.0, Industrial Revolution (IR 4.0) offer a great business opportunity for the SMEs to adjust the business landscape from the traditional to a digitalize. It is because SMEs are the important ‘engines of growth’ for developed and developing countries. They are the main share of total enterprises and contributes significantly to the Gross Domestic Product (GDP), employment and export. However, they are remained unable to achieve expected success, grapple with the failure risk, survival downturns and uncertainty environment. Therefore, to overcome these challenges, this study opens up a new avenue for the SMEs to leverage crowdsourcing practices in order to sustain the business performance and to minimize the COVID-19 outbreak. The aim of this study to investigate the mediating effect of crowdsourcing resources, crowdsourcing practices and SMEs performance. The study employs quantitative approach. The finding indicates that, crowdsourcing serves useful resources to the SMEs to enhance the business performance via harnessing the “wisdom of crowd” and turn the external resources into internal organizational resources. The study also highlights both practical and theoretical implications as well as limitation of the study.